Elastic metamaterials making use of chirality - Liu, Xiaoning (Strojniški vestnik, 2016)
Metamaterials are artificially designed composite materials exhibiting unusual physical properties not easily found in nature. In most cases, these properties appear in a wave environment where local resonance comes into play. Therefore the design principle of these metamaterials relies intimately on creation of appropriate local resonances and their interplay with background waves. In this review, we show that the coupling between rotation and bulk deformations of two-dimensional chiral solids is able to provide a unique resonant mechanism in designing elastic metamaterials, and the recent advances in this area will be reviewed. We begin with a metamaterial with a single-negative parameter by integrating a chiral lattice with resonating inclusions, and demonstrate that this metamaterial not only is suitable for broadband vibration isolation but also provides a mixed-type resonance due to microstructure chirality. This mixed-type resonance is further explored to realize elastic metamaterial with double-negative parameters, which can refract elastic wave with a negative refraction angle. Finally, we present also recent development on micropolar constitutive models, which are potentially suitable for modeling chiral elastic metamaterials.
Keywords: dejanska lastnost; elastični metamateriali; kiralne trdne snovi; negativen lom; razširjanje valov; teorija mikropolarnosti